Maldives - Country Economic Update : Sustaining Robust Development - World Bank (Washington, DC, 2013)
The people of the Maldives have made substantial progress over the past two decades, as reflected in rising incomes and improving social indicators. This report provides an update on this progress, with an integrative analysis of the Maldivian economy, including recent economic developments, macroeconomic policies, and prospects for growth and poverty reduction. In seeking to become an upper middle income country, the Government of Maldives (GoM) will need to address several key development issues while managing the associated fiscal impacts, which is a core theme of the report. These issues include mitigating vulnerability, fostering private sector led growth, strengthening land management and housing finance, developing focus islands to lower the marginal cost of service provision, and improving fiscal systems.